2003
DOI: 10.4278/0890-1171-17.6.361
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Year Stage of Change Evaluation of Dietary Fat and Fruit and Vegetable Intake Behaviors of Cardiac Rehabilitation Patients

Abstract: Cardiac rehabilitation patients are in different stages for two food behaviors linked to the same illness. Results support the appropriateness of nutrition education that emphasizes instrumental information for affecting fat reduction behaviors. Modifying fruit and vegetable intake behaviors is more appropriately addressed with noninstrumental interventions that emphasize health benefits and barriers to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…Over one-third of respondents were in the preparation stage of change. While this is unusual for most proactively recruited samples [25] it is consistent with other fruit and vegetable staging results [40,27]. Next, cross-sectional comparisons of individuals in different stages showed significant differences for fruit and vegetable consumption and self efficacy as well as related constructs from the Theory of Planned Behavior including attitude, intention, subjective norm and perceived behavioral control.…”
Section: Discussionsupporting
confidence: 83%
“…Over one-third of respondents were in the preparation stage of change. While this is unusual for most proactively recruited samples [25] it is consistent with other fruit and vegetable staging results [40,27]. Next, cross-sectional comparisons of individuals in different stages showed significant differences for fruit and vegetable consumption and self efficacy as well as related constructs from the Theory of Planned Behavior including attitude, intention, subjective norm and perceived behavioral control.…”
Section: Discussionsupporting
confidence: 83%
“…Previous randomized controlled trials have shown that complex cognitive-behavioral interventions result in a decrease in fat consumption among individuals who are at risk for coronary heart disease [24,25], patients with coronary artery disease [26], or patients enrolled in cardiac rehabilitation [27]. These findings were obtained for followup periods of up to 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly a reduction in dietary fat intake is not uncommon amongst cardiac patients. In a study of patients enrolled in a CR program, 83% of patients were in either the action or maintenance stages of change in relation to dietary fat intake at the baseline assessment (prior to the commencement of CR), suggesting that dietary changes were well underway prior to their event [29]. Cardiac patients are encouraged and supported by both general practitioners and specialists in their attempts to reduce dietary fat intake in accordance with national dietary recommendations [11,12].…”
Section: Discussionmentioning
confidence: 99%